Mechanical properties of mortars containing recycled ceramic as a fine aggregate replacement - Cabrera-Covarrubias, Francisca Guadalupe; Gómez-Soberón, José Manuel; Almaral-Sánchez, Jorge Luis; Arredondo-Rea, Susana Paola; Corral-Higuera, Ramón (Revista de la Construcción. Journal of Construction, 2015)
We study the behavior of mortars where 0%, 10%, 20%, 30%, 50% and 100% of their original natural sand was replaced by ceramic sand in a search of potential new building materials that will help to conserve natural resources and that are environmentally friendly. In this paper, the physical properties of the sands and their derived mortars, including their compressive strength, flexural strength, and shrinkage due to base and total drying, are characterized. Our results show that the compressive and flexural strengths of the recycled mortars decrease proportionally to the amount of natural sand replacement used. A similar behavior is observed for the shrinkage due to drying in mortars with low ceramic substitutions (10%, 20% and 30%). Based on these findings, we believe that the use of mortars made with recycled sand (with substitution contents lower than 30%) could be feasible in applications where the mechanical requirements are low.